Promotion of local food as tourism product in the Cape Coast Metropolis: An explorative research - Richmond Yeboah; Diana Ashie (Heliyon)
The increasing interest in unique and authentic travel experiences has contributed to the growth of culinary tourism within the tourism industry. The study uses the cultural exchange theory to explain the important role of culinary experiences and development of culinary tourism. This study seeks to explore how local cuisines could be promoted as part of the tourism offerings of Cape Coast to boost tourism and local economic development. Specifically, the study explores the significance of food tourism to Cape Coast and investigates the role of local food establishments in enhancing the tourism appeal. To achieve the objectives of the study, qualitative research approach/design was adopted. The exploratory study design and purposive sampling technique were adopted for the study. Thirty-one respondents comprising tourists, traditional catering homes and restaurant operators were interviewed using the interview guide. The study found that food establishments, including restaurants, food vendors, and food markets, play a crucial role in enhancing the tourism appeal of Cape Coast. In that, local food serves as a gateway to the local culture and some food enthusiasts visit Cape Coast because of the nice local cuisines served at local food establishments. It is recommended that the Ghana Tourism Authority and tour operators in Cape Coast should make conscious efforts to promote the different and unique Cape Coast cuisines as part of the tourism products to attract tourists who are interested in food offerings.